Betty Shamieh’s The Black Eyed: An Arab-American Woman Playwright Inverts and Subverts Orientalism - Nancy C. Jones (Athens Journal of Humanities & Arts)
Arab-American playwright Betty Shamieh emerged on the contemporary theatre scene in the early 2000s with an artistic voice and cultural perspective that broke new ground on the American stage. Her early plays were personal stories of family that studied the immigrant experience through the eyes of exclusively Arab-American characters. Shamieh’s writing shifted after the events of 9/11 and resulted in her writing “The Black Eyed”, a play that addresses the Middle East conflict through the stories of four Arab women. Shamieh’s play adjusts the lens through which audiences witness the ArabAmerican experience and confront their Orientalist tendencies. Her cultural investigation rides a razor’s edge of Orientalism; she positions herself as both “us” and “them” within the discourse as she flips the hegemonic power structure. In this essay I use a close reading informed by Edward Said’s theories to examine the ways in which Shamieh inverts and subverts a gendered use of Orientalism in “The Black Eyed’s” themes and characters, using established tropes like the harem, houris, martyrs, violence, and seduction to fuel her project.